1996
DOI: 10.1093/oxfordjournals.aje.a008955
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake in Relation to Bladder Cancer among Middle-aged Men and Women

Abstract: This population-based case-control study examined the association between selected nutrients, foods, and diet behaviors and bladder cancer. Bladder cancer cases (n = 262) were identified from the Surveillance, Epidemiology, and End Results Program cancer registry for western Washington, and controls (n = 405) were identified through random digit dialing. Cases were diagnosed between January 1987 and June 1990, and eligible subjects were Caucasian, aged 45-65 years, and residents of King, Pierce, or Snohomish c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
5
5

Year Published

2000
2000
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 28 publications
5
100
5
5
Order By: Relevance
“…Two previously conducted population based case-control studies found small increased risks of bladder cancer with increasing intake of dietary vitamin C for men and women combined (Risch et al, 1988) or for men only (Nomura et al, 1991) after controlling for cigarette smoking. However, other population based case control studies presented decreased risks for men and women combined (Bruemmer et al, 1996) or for women only (Nomura et al, 1991), or found no association at all (Riboli et al, 1991). One prospective study suggested an inverse association with dose of vitamin C supplement use, but not with dietary vitamin C intake (Michaud et al, 2000), which is in correspondence to the results of the present study.…”
Section: Vitamins Carotenoids and Bladder Cancer Risk 981supporting
confidence: 81%
See 1 more Smart Citation
“…Two previously conducted population based case-control studies found small increased risks of bladder cancer with increasing intake of dietary vitamin C for men and women combined (Risch et al, 1988) or for men only (Nomura et al, 1991) after controlling for cigarette smoking. However, other population based case control studies presented decreased risks for men and women combined (Bruemmer et al, 1996) or for women only (Nomura et al, 1991), or found no association at all (Riboli et al, 1991). One prospective study suggested an inverse association with dose of vitamin C supplement use, but not with dietary vitamin C intake (Michaud et al, 2000), which is in correspondence to the results of the present study.…”
Section: Vitamins Carotenoids and Bladder Cancer Risk 981supporting
confidence: 81%
“…With respect to bladder cancer, most epidemiological studies support a possible protective effect of vegetable (Bruemmer et al, 1996;D'Avanzo et al, 1995;Michaud et al, 1999;Mills et al, 1991;Negri et al, 1991) and fruit consumption (Bruemmer et al, 1996;Chyou et al, 1993;Negri et al, 1991;Shibata et al, 1992), although some studies have reported no association for vegetable (Riboli et al, 1991;Shibata et al, 1992) or fruit consumption (Michaud et al, 1999;Riboli et al, 1991). There are many candidate agents in fruits and vegetables that influence bladder cancer risk, including carotenoids, vitamin C, vitamin E, and folate.…”
mentioning
confidence: 99%
“…In this study, a quantitative food use questionnaire was administered to participants and assistance was offered to those who had difficulty understanding the questions. While we cannot exclude the possibility that the lack of association may be due to misclassification, it is unlikely that there would be more misclassification in this study than in previous studies that have observed inverse associations using similar dietary assessments (Mills et al, 1991;Shibata et al, 1992;Bruemmer et al, 1996). Confounding by occupational exposures may have occurred if men in high-risk occupations consumed more fruits and vegetables than the rest of the population.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, the association was not observed among smokers, although there was limited power for this analysis. Vitamin E supplement use has been inversely related to bladder cancer risk in two other case -control studies with supplement data (Shibata et al, 1992;Bruemmer et al, 1996) (although only the latter was statistically significant). In addition, although statistically insignificant, our results are consistent with a small decrease in risk among high vitamin E consumers.…”
Section: Fruit and Vegetables And Bladder Cancer Risk Ds Michaud Et Almentioning
confidence: 92%
See 1 more Smart Citation